The salivary microbiome as an indicator of carcinogenesis in patients with oropharyngeal squamous cell carcinoma: A pilot study - Axel Wolf (Nature Portfolio, 2017)
Abstract This study aimed to undertake an initial, comparative analysis of the oral salivary microbiome of patients with oral and oropharyngeal squamous cell carcinoma versus healthy controls. This project, conceived as a pilot study, included 11 patients (1 female, 10 male, mean age 61.6 yrs., SD = 8.2 yrs.) and 11 healthy controls (1 female, 10 male, mean age 46.7 yrs., SD = 15.1 yrs.). Samples of saliva were analysed by high-throughput sequencing of the 16S rRNA gene using the MiSeq platform. Sequence data revealed microbial changes that may mirror disease progression and reflect clinical preconditions such as age, alcohol consumption, tumour size, lymph node status, smoking habit, and tumour HPV-positivity. Consequently, mapping microbial changes in patients with oral and oropharyngeal squamous cell carcinomas might improve our understanding of the pathobiology of the disease, and help in the design of novel diagnostic and treatment strategies.